Android Apps for Absolute Beginners - Jackson, Wallace (Apress : Imprint: Apress, 2012)
Anybody can start building simple apps for the Android platform, and this book will show you how!  Recently updated to include Android Jelly Bean, Android Apps for Absolute Beginners, Second Edition takes you through the process of getting your first Android apps up and running using plain English and practical examples. This book cuts through the fog of jargon and mystery that surrounds Android apps development, and gives you simple, step-by-step instructions to get you started.  Teaches Android application development in language anyone can understand, giving you the best possible start in Android development Provides simple, step-by-step examples that make learning easy, allowing you to pick up the concepts without fuss Offers clear code descriptions and layout so that you can get your apps running as soon as possible This book is Android Jelly Bean compliant, but is backwards compatible to most of the previous Android releases. .